2010
DOI: 10.1093/nar/gkq229
|View full text |Cite
|
Sign up to set email alerts
|

Small RNA class transition from siRNA/piRNA to miRNA during pre-implantation mouse development

Abstract: Recent studies showed that small interfering RNAs (siRNAs) and Piwi-interacting RNA (piRNA) in mammalian germ cells play important roles in retrotransposon silencing and gametogenesis. However, subsequent contribution of those small RNAs to early mammalian development remains poorly understood. We investigated the expression profiles of small RNAs in mouse metaphase II oocytes, 8–16-cell stage embryos, blastocysts and the pluripotent inner cell mass (ICM) using high-throughput pyrosequencing. Here, we show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
115
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(123 citation statements)
references
References 49 publications
8
115
0
Order By: Relevance
“…Therefore, it is apparent that different types of small RNAs vary during spermatogenesis in a wellcoordinated manner. A similar change in major small RNA classes also occurs during pre-implantation development (Ohnishi et al 2010).…”
Section: Discussionmentioning
confidence: 60%
“…Therefore, it is apparent that different types of small RNAs vary during spermatogenesis in a wellcoordinated manner. A similar change in major small RNA classes also occurs during pre-implantation development (Ohnishi et al 2010).…”
Section: Discussionmentioning
confidence: 60%
“…Several studies have suggested that endogenous siRNAs against TEs play an important role in TE silencing [33][34][35][36]. Despite that this endogenous siRNA silencing system is functional in zygotes [37], certain classes of TEs somehow find a way to escape this silencing system for their activation in zygotes.…”
Section: Tet3-mediated 5mc Oxidation Is Dispensable For Zygotic Gene mentioning
confidence: 99%
“…The dynamic changes in the expression of miRNAs in preimplantation embryos (6)(7)(8) and the increased synthesis of miRNAs after the two-cell stage in mouse embryos (7,9) suggest that miRNAs have a functional role in the preimplantation period. This evidence is supported by the observations that mouse oocytes without the miRNA-processing enzyme Dicer have a minimal amount of miRNA, that their resulting zygotes cannot pass through the first cleavage division (7), and that Dicer-null embryos carrying maternal dicer die at embryonic day 7.5 (E7.5) (10).…”
mentioning
confidence: 99%